Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1160/th08-12-0825
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous pathogenic processes of thrombotic microangiopathies in patients with connective tissue diseases

Abstract: To clarify the pathogenic processes of thrombotic microangiopathies (TMAs) in patients with connective tissue disease (CTD), we analysed clinical characteristics and plasma ADAMTS13 levels in 127 patients with CTD-TMAs, including patients with systemic lupus erythematosus (SLE), systemic sclerosis, polymyositis/dermatomyositis, and rheumatoid arthritis (RA), and 64 patients with acquired idiopathic thrombotic thrombocytopenic purpura (ai-TTP). Plasma levels of ADAMTS13 activity, antigen, and inhibitors were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 48 publications
3
83
2
5
Order By: Relevance
“…TTP may occur rarely in conjunction with systemic lupus [82]. This is usually associated with severe deficiency of ADAMTS13 activity and with the presence of anti-ADAMTS13 IgG antibodies [83].…”
Section: Reviewmentioning
confidence: 99%
“…TTP may occur rarely in conjunction with systemic lupus [82]. This is usually associated with severe deficiency of ADAMTS13 activity and with the presence of anti-ADAMTS13 IgG antibodies [83].…”
Section: Reviewmentioning
confidence: 99%
“…Western blot studies of the patient's plasma, which had been stored at -80 , and the purified plasma-derived ADAMTS13, clearly identified that the immunoglobulin type of the inhibitor was IgG (6) (Fig. 1, inset).…”
Section: F I G U R E 1 Cl I N I C a L C O U R S E O F I N F L U E Nmentioning
confidence: 99%
“…They concurrently occur in autoimmune diseases [28], and several cases associated with ANCA-associated vasculitis [29], ''pure'' anti-GBM antibody disease, and ''double positive'' disease have been reported [30]. In most of these cases, as well as present case, ADAMTS-13 activity is moderately decreased and the ADAMTS-13 inhibitor is negative [28][29][30]. Therefore, hemolytic uremic syndrome and thrombotic microangiopathy are supposed to develop following severe vascular endothelial damage [29].…”
Section: Discussionmentioning
confidence: 99%